Gatekeeping in German Primary Health Care - Impacts on Coordination of Care, Quality Indicators and Ambulatory Costs - Sarah M. Hofmann; Andrea M. Muehlenweg (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2016)
Evaluation studies on gatekeeping in primary care exist for a variety of countries but provide mixed evidence on utilization and quality of care as well as costs. Our study evaluates the German gatekeeping program, based on claims data of a major statutory health insurance company. The panel structure of the data allows controlling for patients' characteristics in the year before opting (or not opting) for a GP contract. In contrast to previous studies we are able to draw on multiple identification strategies. We exploit variation in the regional provision of gatekeeping in an instrumental variable (IV) framework. We also analyze GP fixed effects based on the observation of patients opting for one of two different contracts within the same GP office. We find that the gatekeeping contract yields a somewhat higher coordination of care, improved quality (regarding prevention and avoidance of hospitalization) but also higher ambulatory costs. The effects are largely robust between our identification strategies.
Keywords: I10; I11; I13; 330; primary health care; gatekeeping; health care quality